Comparison of conventional culture and automated blood culture system for microbiologic diagnosis of pleural infection - Young Ho Lee; Min Seo Kang; Jinyoung Yang; Si-Ho Kim; Jae-Hoon Ko; Sun Young Cho; Tae Yeul Kim; Hee Jae Huh; Nam Yong Lee; Cheol-In Kang; Doo Ryeon Chung; Kyong Ran Peck; et al. (Microbiology Spectrum)
ABSTRACT Microbiological diagnosis of pleural infection is often hindered by the low sensitivity of conventional culture. The automated blood culture system (ABCS) has been shown to improve diagnostic sensitivity for the culture of non-blood specimens. This study examined the additional diagnostic benefit of ABCS against conventional bacterial culture in patients who underwent thoracentesis or percutaneous drainage. Non-duplicate patients whose pleural fluid samples were tested using both conventional culture and ABCS (BACT/ALERT 3D and VIRTUO, bioMerieux) from 2001 through 2021 were included. Cases were excluded if only contaminants such as coagulase-negative staphylococci, Corynebacterium species, and Bacillus species were identified. Data on culture results, demographics, and laboratory tests were collected. Of the 9,020 patients, 632 patients had positive results in ABCS after excluding those considered contaminants (n = 180) or those positive only in conventional culture (n = 5). Conventional culture was positive in 302 (47.8%) patients, whereas 330 (52.2%) patients had isolates only from ABCS. Patients with positive results from ABCS alone had lower pleural fluid lactate dehydrogenase and serum C-reactive protein (CRP) and higher pleural fluid glucose and protein. Among organisms isolated from ABCS alone, viridans group streptococci, Staphylococcus aureus, and Klebsiella spp. were the most common organisms identified. Higher pleural fluid glucose and blood white blood cells and lower CRP were significant factors associated with exclusive ABCS positivity. More than half of the patients whose pleural fluid cultures were positive using ABCS had a negative result on conventional culture. Our results suggest that ABCS might enhance the microbiologic diagnosis of pleural infection.IMPORTANCEThis study demonstrated that an automated blood culture system (ABCS) has superior sensitivity in pleural infections compared with conventional culture. By comparing both methods in over 9,000 patients, researchers found that ABCS detected bacteria in approximately twice as many cases as conventional culture, especially in patients with a high probability of pleural infection. The findings suggest that ABCS can be a valuable tool in improving the accuracy of diagnosing pleural infections, which could lead to better treatment decisions and patient outcomes.